Group A Streptococcus Subcutaneous Infection-Induced Central Nervous System Inflammation Is Attenuated by Blocking Peripheral TNF - Liu, Ya-Hui; Wu, Pei-Hua; Kang, Chih-Cheng; Tsai, Yau-Sheng; Chou, Chuan-Kai; Liang, Chung-Tiang; Wu, Jiunn-Jong; Tsai, Pei-Jane (Frontiers in Microbiology, 2019)
Group A streptococcus (GAS) infection causes a strong inflammatory response associated with cytokine storms, leading to multiorgan failure, which is characterized as streptococcal toxic shock syndrome. However, little is known about GAS subcutaneous infection-mediated brain inflammation. Therefore, we used a bioluminescent GAS strain and reporter mice carrying firefly luciferase under transcriptional control of the nuclear factor-kappa B (NF-κB) promoter to concurrently monitor the host immune response and bacterial burden in a single mouse. Notably, in addition to the subcutaneous inoculation locus at the back of mice, we detected strong luminescence signals from NF-κB activation and increased inflammatory cytokine production in the brain, implying the existence of central nervous system inflammation after GAS subcutaneous infection. The inflamed brain exhibited an increased expression of glial fibrillary acidic protein and nicotinamide adenine dinucleotide phosphate oxidase components and greater microglial activation and blood–brain barrier (BBB) disruption. Furthermore, Fluoro-Jade C positive cells increased in the brain, indicating that neurons underwent degeneration. Peripheral tumor necrosis factor (TNF), which contributes to pathology in brain injury, was elevated in the circulation, and the expression of its receptor was also increased in the inflamed brain. Blockage of peripheral TNF effectively reduced brain inflammation and injury, thereby preventing BBB disruption and improving survival. Our study provides new insights into GAS-induced central nervous system inflammation, such as encephalopathy, which can be attenuated by circulating TNF blockage.